Development of a 2-D Wavelet Transform based on Kronecker Product - Mahmoud, Waleed A; Hadi, Ahmed S; Jawad, Talib M (Al-Nahrain Journal of Science, 2012)
Advances in wavelet transform have produces algorithms capable of surpassing the existing digital signal processing. This paper presents a new wavelet transform computation method that verifies the potential benefits of the kronecker product and gains much improvement in terms of low computational complexity. A fast algorithm for computing 2-D wavelet transform based on a modified orthogonal matrix is developed using kronecker product. The algorithm has several promising features which make it suitable for 2-D signal processing applications.